Regulation of Nir gene in Lactobacillus plantarum WU14 mediated by GlnR - Qiu, Hulin; Chang, Xiaoyu; Luo, Yan; Shen, Fengfei; Yin, Aiguo; Miao, Tingting; Li, Ying; Xiao, Yunyi; Hai, Jinping; Xu, Bo (Frontiers in Microbiology, 2022)
Nitrogen (N) is an essential element in the biosynthesis of key cellular components, such as proteins and nucleic acids, in all living organisms. Nitrite, as a form of nitrogen utilization, is the main nutrient for microbial growth. However, nitrite is a potential carcinogen that combines with secondary amines, which are breakdown products of proteins, to produce N-nitroso compounds that are strongly carcinogenic. Nitrite reductase (Nir) produced by microorganisms can reduce nitrite. Binding of GlnR to the promoter of nitrogen metabolism gene can regulate the expression of Nir operon. In this study, nitrite-resistant L. plantarum WU14 was isolated from Pickles and its protease Nir was analyzed. GlnR -mediated regulation of L. plantarum WU14 Nir gene was investigated in this study. New GlnR and Nir genes were obtained from L. plantarum WU14. The regulation effect of GlnR on Nir gene was examined by gel block test, yeast two-hybrid system, bacterial single hybrid system and qRT-RCR. Detailed analysis showed that GlnR ound to the Nir promoter region and interacted with Nir at low nitrite concentrations, positively regulating the expression of NIR. However, the transcription levels of GlnR and Nir decreased gradually with increasing nitrite concentration. The results of this study improve our understanding of the function of the Nir operon regulatory system and serve as the ground for further study of the signal transduction pathway in lactic acid bacteria.